Karakteristik Ekstrak Kulit Tanduk Kopi Arabika (Coffea Arabica L.) Sebagai Sumber Antioksidan Pada Variasi Jenis Pelarut Dan Daya Ekstraksi Mengggunakan Microwave Assisted Extraction - Satya, I Gede Made; Putra, Gusti Putu Ganda; Anggreni, Anak Agung Made Dewi (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI, 2025)
The parchment skin of Arabica coffee is a by-product of the hulling process that contains bioactive compounds such as phenols and flavonoids, which have potential as natural antioxidants. This study aims to determine the effect of solvent type and extraction power using Microwave Assisted Extraction (MAE) on the characteristics of Arabica coffee parchment extract (Coffea arabica L.), as well as to identify the best treatment combination for producing extracts with high antioxidant potential. A factorial Completely Randomized Design (CRD) was used with two factors: the type of solvent (ethanol, methanol, and acetone) and extraction power (300, 450, and 600 watts). The data were analyzed using analysis of variance (ANOVA), followed by the Honest Significant Difference (HSD) test. The results showed that the type of solvent, extraction power, and their interaction had a highly significant effect on extract yield, total phenolic content, and total flavonoid content, while a significant effect was observed on antioxidant capacity. The best treatment was obtained using ethanol as the solvent and an extraction power of 600 watts, resulting in an extract yield of 6.06 ± 0.15%, total phenolic content of 2.83 ± 0.0293 mg GAE/g, total flavonoid content of 7.86 ± 0.01 mg QE/g, and antioxidant capacity of 0.48 ± 0.011 mg GAEAC/g.